Enhancement the added value of sengon wood waste pulp as bioenergy raw material for bioethanol production. Issue 1 (January 2020) - Winarni, I; Bardant, TB; Hendra, D
Abstract: Lignocellulosic are renewable and abundant, and estimate to be produced in10-50 billion tons/year as dry matter. Cellulose component in lignocelluloses can be converted into glucose as a feedstock for ethanol fermentation. This paper contains of research results of sengon waste pulp convertion became glucose and ethanol by enzymatic hydrolysis and the purpose of this study was to obtain information on the optimum conditions of treatment to produce high ethanol content of sengon waste pulp using the Response Surface Methodology (RSM) method and high loading substrate. Response surface methodology based on a three level, three variable Central Composite Rotable Design (CCRD) was used to evaluate the interactive effect of Tween 20 concentration (0-2%), cellulase concentration (10-15 FPU/g substrate-dw) and substrate loading (20-35% dw). The results showed the highest ethanol content (15.2%) with addition 35% of substrate; 15 FPU/g substrate of enzyme and 1% Tween 20 with equations : Y = -66, 551 + 0.491X1 + 10.794 X2 – 0.025 X12 - 0.472 X22 - 1, 549 X32 + 0.065 X1X2 + 0.234 X1X3 – 0.086 X2X3. So that the use of the RSM method can know quickly which combination of treatments can produce high ethanol levels through the resulting equation. Distinctive dosages of each variable within these ranges need to be matched to each other according to resulted mathematical formula from RSM to give optimum condition points. Several optimum condition points had been validated and ethanol concentration higher than 18%v in the fermentation broth had been achieved with acuration of equation (R 2 ) 0.97.